(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تناولت هذه الدراسة تحديد تركيز نزر عنصري الكادميوم والرصاص في دقائق الغبار المُترسبة على أوراق شجرتي الإكيدنيا (ورق خشن) والمطاط (ورق أملس)، في مواقع ذات نشاط بشري وازدحام مروري ومشاريع إنشائية (كراج الفاروس، دوارهارون، دوار اليمن) في الأيام الآتية: -15/6/2006 - 20,30/5/2006 - 20/4/2006 15/7/2006 - 15,30/8/2006، وتمًّ جمع عينات من منطقة بعيدة عن مصادر التلوث خارج مدينة اللاذقية (الشاطئ الأزرق)، في الأيام اﻵتية:20,30/8/2006 - 15/7/2006 - 15/6/2006 - 20,30/5/2006. أجريت الدراسة باستخدام جهاز امتصاص ذري من نوع SHIMADZU AA –6800. أظهرت النتائج أن تراكيز نزر عنصر الكادميوم بلغت أعلى قيمة لها على أوراق أشجار المطاط والإكيدنيا (0.034ppb/cm2) في 15,30/8/2006 في دوار اليمن، وللرصاص (3.022ppb/cm2) و(2.519ppb/cm2) في 30/8/2006 في كراج الفاروس ودوار اليمن على التوالي، أما أدنى القيم فسجلت بالنسبة لعنصر Cd (0.001ppb/cm2) و(0.003ppb/cm2) في 20/5/2006 و 20/4/2006 في موقع الشاطىء الأزرق وكراج الفاروس على التوالي، ولعنصر Pb (0.089ppb/cm2) و(0.135ppb/cm2) بتاريخ 20/5/2006 في موقع الشاطئ الأزرق، أما في بقية المواقع فتراوحت قيم التركيز للعنصرين المدروسين ما بين القيمتين الدنيا والعليا. This study involves the determination of trace cadmium and lead concentrations in suspended dust particles, which accumulated on leaves of rubber and akeedenia trees, from human activity locations and traffic jams: (Garage faros, Dawar yaman, Dawar haroon), in the following days: 20/4/2006, 20,30/5/2006, 15/6/2006, 15/7/2006, 15,30/8/2006. Samples for comparison were taken from a far location of human pollution sources (Blue beach) in the following days: 20/5/2006, 30/5/2006, 15/6/2006, 15/7/2006, 15/8/2006, 30/8/2006. This study was performed by AAS-technique using (AA-6800 SHIMADZU). The results show that the concentrations of cadmium had achieved the maximum value on rubber and akeedenia tree leaves (0.034ppb/cm2) in 15,30/8/2006 in Dawar yaman, and for Lead (3.022ppb/cm2)&(2.519ppm/cm2) in 30/8/2006 in Garage faros & Dawar yaman respectively, whereas the minimum value was recorded for cadmium (0.001ppb/cm2) & (0.003pp/cm2) on 20/5/2006 & 20/4/2006 in Blue Beach and Garage faros locations respectively, and for Lead (0.089ppb/cm2)&(0.135ppm/cm2) on 20/5/2006 in Blue Beach locations. In the other locations, the value of concentration ranged between the max. and min. values for the two elements.